2008
DOI: 10.1159/000139611
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Bacterial Involvement in Severe Acute Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: Background: Strategies aiming at reducing antibiotic use are required in the intensive care unit (ICU). Although antibiotic treatment is recommended in patients with severe exacerbation of chronic obstructive pulmonary disease (COPD), a bacterial etiology is found in only a half of these patients. Objectives: The aim of this study was to determine factors predicting bacterial isolation in severe acute exacerbations of COPD. Methods: All patients with severe acute exacerbation of COPD requiring intubation and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 69 publications
0
34
0
2
Order By: Relevance
“…In a study done in hospitalized COPDE patients, 76% had antibiotic therapy, but if the threshold of PCT <0.25 ng/ml had been used, treatment would have been given to only 7% of them [28]. Nseir et al [44] reported that PCT >0.5 ng/ml with a positive Gram stain for endotracheal aspirate was associated with bacterial exacerbations. In a multicenter randomized controlled study from Italy, the authors compared 10 days of antibiotic treatment with discontinuation of antibiotics within 3 days plus PCT guidance in patients hospitalized for COPDE [20].…”
Section: Discussionmentioning
confidence: 99%
“…In a study done in hospitalized COPDE patients, 76% had antibiotic therapy, but if the threshold of PCT <0.25 ng/ml had been used, treatment would have been given to only 7% of them [28]. Nseir et al [44] reported that PCT >0.5 ng/ml with a positive Gram stain for endotracheal aspirate was associated with bacterial exacerbations. In a multicenter randomized controlled study from Italy, the authors compared 10 days of antibiotic treatment with discontinuation of antibiotics within 3 days plus PCT guidance in patients hospitalized for COPDE [20].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18] From studies evaluating the parameters associated with bacterial colonization, a significant relationship was found between the frequency of exacerbations and increased colonization. 14,19 There are studies showing correlation between the decrease in FEV1 and the colonization. 16 As a result, in patients with frequent exacerbation, bacterial colonization seems to be more common.…”
Section: Etıology Of Exacerbatıonsmentioning
confidence: 99%
“…The positive predictive value of the combination of a positive Gram stain and PCT 1 0.5 ng/ ml drops from 93.1 to 58% in the frequent situation of a previous intake of antibiotics [6] . Another aspect is the Increasing resistance of respiratory pathogens to the usual treatments is caused by the abuse of antibiotics.…”
mentioning
confidence: 93%